A new species of the lichen genus Lepraria (Lecanorales: Stereocaulaceae) from Pakistan - Wahab, Hira; Wahab, Afshan; Anwar, Ayesha; Uddin, Siraj; Alwahibi, Mona S; Elshikh, Mohamed S; Ahmad, Shabir; Iqbal, Rashid; Khalid, Abdul Nasir (Phytotaxa, 2025)
Lepraria malakandensis is described as new to science, based on morpho-anatomical, chemical, and phylogenetic investigations. The new taxon is characterized by leprose, white-grey to greenish-grey thallus with atranorin, zeorin, stictic acid, and constictic acid. Phylogenetic study of available sequencing data unambiguously distinguishes L. malakandensis from other species in the genus. A detailed description, illustrations and a comparison with related taxa is also provided.